A review of methods to calculate current and future evaporation rates from pit lakes with high concentrations of total dissolved solids - Lindauer, J; Byers, S; Lehn, G; Evans, E; Castendyk, D; Moravec, B (Mine Closure 2023: 16th International Conference on Mine Closure, 2023)
For pit lakes in arid environments, lake evaporation and mechanical evaporation methods (e.g., misters) are sometimes used to manage water levels to avoid discharge to the receiving environment (e.g., aquifers). For terminal lakes, the steady-state water surface elevation remains below the regional water table. This creates a perpetual sink in the local water table such that the pit retains mine impacted water on site. One management strategy for flow-through lakes involves enhancing evaporation using misters to prevent the lake from reaching its steady state water level, thereby producing an artificial terminal pit lake. Evapo-concentration coupled with the deposition of mister-generated aerosols landing within the pit catchment can increase the concentration of total dissolved solids (TDS) in lake water over time. As TDS concentration increases, the activity of water decreases, reducing the vapor pressure and decreasing the evaporation rate. Consequently, the long-term management plan and water balance for artificial terminal lakes must account for TDS concentrations in future projections of evaporation rates. This review evaluates methods to calculate current and future evaporation rates, including methods that consider the impact of TDS concentrations on the activity of water. First, we review methods used to estimate current evaporation rates, including: (1) pan evaporation, (2) water balance, (3) energy balance, (4) combination mass transfer and energy balance method (called ‘combination method’, e.g. Penman equation), (5) pan and combination method (called ‘PenPan’), (6) water isotope mass balance, (7) temperature-only models [e.g. the Hargreaves and Samani (H-S) equation], and (8) eddy covariance measurements. Next, using a modified Penman equation paired with an ocean water equation of state, we showed how increased TDS concentrations in a theoretical lake can reduce the activity of water and estimated evaporation rate. Results of this exercise showed that simulated evaporation was greatly impacted above TDS concentrations of 300,000 mg/L. For long term management plans and water balances that utilize predictions of future evaporation rates, it is preferred to use a method like the H-S equation since it requires only downscaled temperature from a climate projection, whereas the modified Penman requires wind speed, relative humidity and other meteorologic variables which are not typically generated by climate projections and have greater uncertainty. To show how a H-S equation can be modified to account for TDS concentrations, we used the modified Penman to establish the coefficients for TDS and site conditions to establish a modified H-S equation. Key Words: Evaporation, Total Dissolved Solids, Modified Penman equation, Modified Hargreaves and Samani equation For pit lakes in arid environments, lake evaporation and mechanical evaporation methods (e.g., misters) are sometimes used to manage water levels and avoid flow conditions and/or lake water discharge to receiving environments (e.g., aquifers). Evaporation coupled with the deposition of mister-generated aerosols within the pit catchment can increase the concentration of total dissolved solids (TDS) in lake water over time. As TDS concentrations increase, the activity of water decreases, reducing the vapor pressure and the evaporation rate. Consequently, for long-term water balances and closure plans for pit lakes with high TDS concentrations, it is important to account for TDS concentration effects on evaporation rates. Accurate evaporation rates are notably important for pit lakes that are actively managed using enhanced evaporation to prevent the surface water level from reaching steady state conditions. All pit lakes are initially terminal sinks, and many become flow-through systems after the lake surface rises above the surrounding water table. Enhanced evaporation is a useful short term management approach that can maintain artificial terminal conditions in pit lakes, but forecasts of long-term water management with this approach require an accurate prediction of future evaporation rates that accounts for TDS. This review evaluates the strengths, assumptions, and limitations of methods to calculate current and future evaporation rates, including methods that consider meteorological conditions, heat storage, and the impact of TDS concentrations on the activity of water. First, we review methods used to estimate current evaporation rates, including: (1) pan evaporation, (2) water balance, (3) energy balance, (4) combination mass transfer and energy balance method (called ‘combination method’, e.g. Penman equation), (5) pan and combination method (called ‘PenPan’), (6) water isotope mass balance, (7) temperature-only models [e.g. the Hargreaves and Samani (H-S) equation], and (8) eddy covariance measurements. Next, we applied a commonly used evaporation estimation method (i.e., Penman) with an ocean water equation of state to show how TDS concentrations lead to reductions in the evaporation rate, with more substantial reductions in the evaporation rate occurring beyond a TDS concentration of 150,000 mg/L. Finally, we provide an example of predicted future evaporation rates using a novel, temperature-dependent, modified Hargreaves and Samani (H-S) equation. Water management plans for terminal and artificially terminal pit lakes involve minimizing the likelihood that water will discharge from the pit lake to downgradient aquifers. In arid climates, predictive water balances used to forecast lake water levels must account for TDS-corrected evaporation rates. This study reviewed common methods used to calculate current evaporation rates, and presented a novel, temperature-based approach to calculate future evaporation rates from TDS concentrations and temperature, called the modified Hargreaves and Samani equation (modified H-S). To apply the modified H-S method, one needs (1) future temperatures predicted from a climate model; (2) the activity of water predicted from past and future TDS concentrations; and (3) TDS and Site coefficients calculated from historic site meteorological data using the modified Penman equation. A hypothetical scenario for a pit lake located in an arid climate showed that evaporation rates begin to more greatly decrease around TDS concentrations of 300,000 mg/L. By integrating the modified H-S equation into a pit lake water balance, pit lake managers can anticipate the point in time when current water management strategies (e.g., demisters) will no longer be sufficient to contain water on site and can plan for new management strategies.